Correlation Between Family Support and Adherence to Insulin Therapy in Patients with Type 2 Diabetes Mellitus - Jurdiansyah, Jurdiansyah; Wantonoro, Wantonoro; Ruhyana, Ruhyana (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
Diabetes Mellitus (DM) is a chronic disease caused by the body's inability to use insulin optimally. Insulin therapy is an effective treatment to replace the role of the insulin hormone. Adherence to insulin therapy is crucial for the health of DM patients. This study investigates the correlation between family support and adherence to insulin therapy among type II DM patients at Gamping II Health Center, Yogyakarta. This study employed a quantitative cross-sectional design. Fifty-three type II DM patients who underwent control at Gamping II Health Center participated in this study. The family support instrument was measured using the Hensarling Diabetes Family Support Scale (HDFSS) Indonesian version, while adherence to insulin therapy was measured using the Morisky Insulin Adherence Scale-8 (MIAS). Kendall tau test was used for data analysis. The results showed a significant correlation between family support and adherence to insulin therapy among type II DM patients at Gamping II Health Center (p=0.011). Effective family support, in the form of assistance, attention, or information, is crucial in improving adherence to insulin therapy among type II DM patients. Therefore, family involvement is highly recommended to control blood sugar levels among type II DM patients.